DEVELOPMENT OF LEARNING MEDIA DESIGN OF LESSON PLANS: CURRICULUM 2013 REVISED 2018 - Intannisa Nazwa; Sri Handayani; Shinta Maharani; Dewi Cakrawati (Journal of Development and Integrated Engineering, 2022)
One of the competencies required when carrying out Education Unit Introduction Program (PPLSP)is the ability to compile a Learning Implementation Plan (RPP). The dynamic development of the curriculum requires students to always update information about the curriculum.The purpose of this study was to develop an android-based learning media for the preparation of lesson plans using the 2013 revised 2018 curriculum and to determine the feasibility of the learning media. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) method is used in the development of learning media. Media feasibility is assessed by media experts, materials experts, and users. The assessment refers to eight aspects of media selection; (1) the suitability of the media with the learning objectives, (2) the suitability of the characteristics of students, (3) can be a source of learning, (4) the efficiency and effectiveness of the use of media, (5) safety for students, (6) the ability of the media in developing activeness and learner creativity, (7) the ability of the media in developing a pleasant learning atmosphere, and (8) the quality of the media. The validation results show that the learning media developed in this study received a fairly decent score from media experts, very feasible from material experts, and feasible based on user responses. The use of learning media for preparing lesson plans is expected to help students understand and make good lesson plans.